Crossing network versus dealer market: Unique equilibrium in the allocation of order flow - Jutta Dönges; Frank Heinemann; Tijmen R. Daniëls (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2013)
The allocation of order flow to alternative trading systems can be understood as a game with strategic substitutes between buyers on the same side of the market, as well as one of positive network externalities. We consider the allocation of order flow between a crossing network and a dealer market and show that small differences in traders' preferences generate a unique switching equilibrium, in which patient traders use the crossing network while impatient traders submit orders directly to the dealer market. Our model explains why assets with large turnovers and low price volatility are likely to be traded on crossing networks, while less liquid assets are traded on dealer markets.
Keywords: C62; G10; G20; 330; trading platform; order flow; strategic complements; strategic substitutes; global game